PENYELESAIAN SENGKETA PERTANAHAN PT. ARARA ABADI YANG DI KLAIM OLEH MASYARAKAT PENDATANG DESA SUNGAI GONDANG KECAMATAN MINAS PROVINSI RIAU - Andrea Sakavino; Maryati Bachtiar; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The purpose of this study is, First, to find out the factors that cause land disputes atPT. Arara Abadi which was claimed by migrant communities from Sungai GondangVillage, Minas District, Riau Province. Second, to find out the obstacles in resolving landdisputes by PT. Arara Abadi which was claimed by migrant communities from SungaiGondang Village, Minas District, Riau Province.This research uses the type of sociological legal research. The sample in this researchis Public Relations of PT. Arara Abadi, Head of DLHK Riau Province, Head of district ofWest Minas, community leaders and the community itself. The analytical tool in this studyis a qualitative method. This study found that there were things that were less than optimalin reality on the ground, so it was necessary to anticipate them with maximum effort.The results of this study, the factors causing land disputes in PT. Arara Abadi, whichwas claimed by migrant communities in Sungai Gondang Village, Minas District, RiauProvince, consisted of several factors. First, because of a certificate issued by anunscrupulous village. Second, there is an acknowledgment that the area has long beenhanded down from generation to generation. Besides that, the constraints in resolving landdisputes by PT. Arara Abadi which is claimed by the people of Sungai Gondang Village,Minas District, Riau Province consists of several points. First, due to the unclear legalityof community land ownership. Second, the reported condition of the land does not matchwhat is claimed with the reality on the ground. Third, there are differences in demandsfrom society. To prevent similar incidents from happening, the important role of PublicRelations is to routinely conduct outreach to the local Village apparatus and thecommunity about the boundaries of the company's territory and the dangers of carryingout illegal activities in forest areas. In order for this problem to be resolved, it is better forthe company's public relations to be more intense in approaching the community andrelated parties so that it is important to preserve forests and respect the provisions thathave been given by the government to companies to manage these forests. Apart from that,other forms of corporate social responsibility can also be carried out with the aim ofcreating welfare for the community and minimizing the loopholes for reclaim by a groupof irresponsible people.Keywords: Land Disputes - Company - Communit